A STUDY TO ASSESS THE EFFECTIVENESS OF INFORMATION BOOKLET ON KNOWLEDGE REGARDING GARDASIL 9 AMONG THE ADOLESCENT GIRLS AT SELECTED RURAL AREA, KANPUR, UP. (International Journal of Food and Nutritional Sciences, 2021)
Gardasil (Merck & Co., Kenilworth, NJ, USA), is the first commercially available HPVvaccine licensed by the United States Food and Drug Administration (FDA), in 2006. Thebivalent HPV vaccine, Cervical (GSK, Brentford, UK) was approved by the EuropeanMedicines Agency (EMA) in 2007 and by the FDA in 2009